(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The study provides detailed investigation of relative and conjoint predictability of coping strategies, parental attachment and social support for the academic stress among teenagers results indicate that coping strategies and parental attachment attributes high conjoint effect collectively them their separate contributions. Neither social support or its any sub-variable were significant contributors towards academic stress,